MODERNIZATION OF THE RUSSIAN DOCTORAL PROGRAMS IN EDUCATION: THE SEARCH OF MODELS IN AN INTERNATIONAL CONTEXT - Vladimir D. Nechaev (Высшее образование в России, 2016)
The article addresses the prospects of modernization of the Russian doctoral programs in education in the context of its internationalization. The author analyzes the challenges that arise in front of the Russian educational postgraduate school in connection with the vector of its modernization and internationalization. Based on the analysis of doctoral programs in education of the world leading universities (top 25 QS rankings in the subject «Education ») and the study of the discussion in the scientific literature, the author identifies the main patterns and trends of development of doctoral programs in education in the modern world. This analysis allows to specify challenges and opportunities that Russian educational postgraduate school faces in the process of modernization and internationalization.